Importance of soil heating, liquid water loss, and vapor flow enhancement for evaporation. Issue 10 (18th October 2016) - Novak, Michael D.
Abstract: Field measurements conducted by Cahill and Parlange (1998) are reanalyzed to verify if their conclusion that daytime peak values of 60–70 W m −2 of latent heat flux divergence occurred in the 7–10 cm soil layer of a drying Yolo silt loam when maximum values of surface latent heat flux are estimated to have been about 100 W m −2 . The new analyses, as similar to theirs as possible, are validated using a numerical simulation of coupled soil moisture and heat flow based on Philip and de Vries (1957) as a test bed. The numerical simulation is extended to include the flow of air induced by diurnal soil heating and evaporative water loss to verify the flux divergence calculations reported in Parlange et al. (1998) that explained the findings of Cahill and Parlange (1998). It is shown that the conclusions of both of these papers are in error, so that the original version of the Philip and de Vries (1957) theory is consistent with their field measurements after all and the effects of airflow associated with soil heating and liquid water loss (and low‐frequency barometric pressure variations also considered) are negligible in practice. In an additional investigation, enhancement of diffusive vapor flow (first postulated by Philip and de Vries (1957)) and discussed extensively in the literature since is shown to have negligible effects on cumulative evaporation under field conditions. Key Points: Cahill and Parlange 's [1998] and Parlange et al .'s [1998] conclusions are both in error Soil heating and barometric pressure fluctuations have negligible effects on evaporation Enhancement of soil vapor diffusion has a negligible effect on evaporation under field conditions